Scaling properties of granular materials - Pöschel, Thorsten; Salueña, Clara; Schwager, Thomas (Physical Review E, 2001)
With the assumption of viscoelastic particle deformation, it is demonstrated that naive scaling modifies the properties of granular systems such that the original system and the scaled system might reveal quite different dynamic properties. To guarantee equivalent dynamical properties of the original and the scaled systems, material properties are modified in accordance with the scaling factor. For demonstration purposes, an example is given where the dynamics of a granular system changes significantly with system size.